Plant Growth Enhancement of Seeds Immersed in Plasma Activated Water. (15th February 2017) - Sarinont, Thapanut; Katayama, Ryu; Wada, Yosuke; Koga, Kazunori; Shiratani, Masaharu
ABSTRACT: We have produced plasma activated water (PAW) using air, O2, N2, He and Ar atmospheric pressure dielectric barrier discharge plasma irradiation to deionized water. Then, PAW was kept for 1 hour or 1 day at room temperature to reduce concentrations of short lifetime reactive oxygen species and reactive nitrogen species before supplying to plants. O2, air and N2 PAW induces growth enhancement of plants. For 1 hour PAW supply the longest seedling length after 3 days cultivation is 1.62, 1.38, 1.13, 1.12, and 1.04 times long for air, O2, He, N2, and Ar plasmas compared with the length for thecontrol, whereas for 1 day PAW supply it is 1.52, 1.28, 1.13, 1.10, and 1.08 times long for air, O2, He, N2 and Ar. Therefore, long lifetime reactive oxygen nitrogen species in PAW is effective for the growth enhancement.